Diabetes Is the Strongest Predictor of Limited Exercise Capacity in Chronic Heart Failure and Preserved Ejection Fraction (HFpEF) - Berisha-Muharremi, Venera; Henein, Michael Y.; Dini, Frank L.; Haliti, Edmond; Bytyçi, Ibadete; Ibrahimi, Pranvera; Poniku, Afrim; Batalli, Arlind; Tafarshiku, Rina; Elezi, Shpend; Bajraktari, Gani (Frontiers in Cardiovascular Medicine, 2022)
Background and Aim: Type 2 diabetes mellitus (T2DM) is a known risk factor in patients with heart failure (HF), but its impact on phenotypic presentations remains unclear. The aim of this study was to prospectively examine the relationship between T2DM and functional exercise capacity, assessed by 6 min walk test (6-MWT) in chronic HF. Methods: We studied 344 chronic HF patients (mean age 61±10 years, 54%female) in whom, clinical, biochemical and anthropometric data were and all underwent echo-Doppler study and a six-minute walk test (6-MWT) in the same day. The 6-MWT distance divided the patients into, Group I: ≤ 300 m and Group II: >300 m. Also, left ventricular (LV) ejection fraction (EF) classified them into HF with preserved EF (HFpEF), and HF with reduced EF (HFrEF). Results: 111/344 (32%) patients had T2DM. These patients had higher prevalence of arterial hypertension (p=0.004), higher waist-hips ratio (p=0.041), higher creatinine (p=0.008) and urea (p=0.003), lower hemoglobin (p=0.001), and they achieved shorter 6MWT distance compared with those with no T2DM. Patients with limited exercise (<300 m) had higher prevalence of T2DM (p˂0.001), arterial hypertension (p=0.004), and atrial fibrillation (p=0.001), higher waist/hips ratio (p=0.041), higher glucose level o (p<0.001), lower hemoglobin (p<0.001), larger left atrium (p=0.018), lower lateral MAPSE (p=0.032), septal MAPSE (p<0.001), and TAPSE (p<0.001), compared to those performing >300 m. In multivariate analysis [odds ratio 95% confidence interval], T2DM [3.147 (1.781 - 5.562), p˂0.001], low haemoglobin [0.816 (0.703 - 0.947), p=0.008], atrial fibrillation [2.563 (1.214 - 5.408), p=0.014], and reduced septal MAPSE [0.338 (0.134 - 0.852), p=0.021], independently predicted the limited 6-MWT distance. The reduced 6-MWT independently predicted diabetes [5.736 (2.554-12.882), p˂0.001], atrial fibrillation [6.377 (1.873-21.439), p=0.003], and septal MAPSE [0.108 (0.025-0.456), p=0.002], in HFpEF patients, whereas hemoglobin [0.792 (0.633-0.991), p=0.041] and TAPSE [0.451 (0.208-0.975), p=0.043] in HFrEF. Conclusion: Predictors of exercise intolerance in patients with chronic HF differ according to LV systolic function, demonstrated as ejection fraction. T2DM seems the most powerful predictor of limited exercise capacity in patients with HFpEF. These findings highlight the necessity of optimum diabetic control in addition to other atherosclerosis risks.